Motion controllers for learners to manipulate and interact with 3D objects for mental rotation training. (9th May 2013) - Yeh, Shih‐Ching; Wang, Jin‐Liang; Wang, Chin‐Yeh; Lin, Po‐Han; Chen, Gwo‐Dong; Rizzo, Albert
Abstract Mental rotation is an important spatial processing ability and an important element in intelligence tests. However, the majority of past attempts at training mental rotation have used paper‐and‐pencil tests or digital images. This study proposes an innovative mental rotation training approach using magnetic motion controllers to allow learners to manipulate and interact with three‐dimensional (3D) objects. Stereovision allows learners to perceive the spatial geometric form of a 3D object. This approach allows learners to perceive 3D objects in space through stereovision and make mental rotation visible from each intrinsic and invisible mental rotation step using motion‐interaction methods. This study examines the effects of user training performance and perceptions. The results indicate that the proposed approach can improve user mental rotation ability effectively. Learners expressed high degrees of concentration toward the mechanism that included direct control and immediate feedback. The results also suggest that female testers perceive greater degrees of playfulness toward the mechanism and improve more through training than male testers.